Synthesis and characterization of siloxane-based polyurethane elastomers using hexamethylene diisocyanate. (November 2015) - Zia, Khalid Mahmood; Ahmad, Aftab; Anjum, Sohail; Zuber, Mohammad; Anjum, Muhammad Naveed
The present research work was performed to study the properties of siloxane-based polyurethane (SPU) elastomers using aliphatic diisocyanate. SPU samples constituting of hexamethylene diisocyanate, hydroxyl-terminated polybutadiene, and polydimethylsiloxane (PDMS) were synthesized by two-step polymerization technique. Molecular engineering and surface characterization were carried out, and the outcome of the results was discussed. The conventional spectroscopic characterization of the synthesized samples using Fourier transform infrared spectroscopy confirms the existence of the proposed SPU structure. Surface properties of the synthesized material were studied determining the percentage of water absorption and equilibrium of the degree of swelling. It was found that by increasing the mole ratio of PDMS, the synthesized PU samples showed hydrophobic behavior while placing them in water and in dimethylsulfoxide solvent.